Improved long-term clinical outcomes in patients with ST-elevation myocardial infarction undergoing remote ischaemic conditioning as an adjunct to primary percutaneous coronary intervention. - Sloth, A; Schmidt, MR; Munk, K; Kharbanda, R; Redington, A; Schmidt, M; Pedersen, L; Sørensen, H; Bøtker, H (2014)
AIMS: Remote ischaemic conditioning as an adjunct to primary percutaneous coronary intervention in patients with ST-elevation myocardial infarction increases myocardial salvage. We investigated the effect of remote ischaemic conditioning on long-term clinical outcome. METHODS AND RESULTS: From February 2007 to November 2008, 333 patients with a suspected first acute ST-elevation myocardial infarction were randomized to receive primary percutaneous coronary intervention with (n = 166) or without (n = 167) remote ischaemic conditioning (intermittent arm ischaemia through four cycles of 5-min inflation followed by 5-min deflation of a blood-pressure cuff). Patient follow-up extended from the randomization date until an outcome, emigration or January 2012 (median follow-up = 3.8 years). The primary endpoint was major adverse cardiac and cerebrovascular events (MACCE)-a composite of all-cause mortality, myocardial infarction, readmission for heart failure, and ischaemic stroke/transient ischaemic attack. The individual components of the primary endpoint comprised the secondary endpoints. Outcomes were obtained from Danish nationwide medical registries and validated by medical record review and contact to patients' general practitioner. In the per-protocol analysis of 251 patient fulfilling trial criteria, MACCE occurred for 17 (13.5%) patients in the intervention group compared with 32 (25.6%) patients in the control group, yielding a hazard ratio (HR) of 0.49 (95% confidence interval: 0.27-0.89, P = 0.018). The HR for all-cause mortality was 0.32 (95% confidence interval: 0.12-0.88, P = 0.027). Although lower precision, the HRs were also directionally lower for all other secondary endpoints. CONCLUSION: Remote ischaemic conditioning before primary percutaneous coronary intervention seemed to improve long-term clinical outcomes in patients with ST-elevation myocardial infarction.